Fuel cell and battery powered light electric vehicle simulation - Sahin, Habip; Cetin, Muhammed Sefa; Gencoglu, Muhsin Tunay; Erdinc, Ozan (Pergamon-Elsevier Science Ltd, 2025)
Electrification in transportation is becoming more widespread day by day due to both environmental and economic concerns. For this purpose, vehicles suitable for many different purposes are designed and put on the market. Although battery electric vehicles are the first solution that comes to mind, their limited energy storage capacity and high charging times pose a major disadvantage. In order to overcome these disadvantages, technologies that use fuel cells as the primary energy source and batteries are used as secondary are also being developed. In this study, a hybrid power source consisting of fuel cell and battery is designed and the control of a brushless direct current motor that is assumed to drive a light electric vehicle is simulated in Matlab/Simulink. The fuel consumption of the simulated vehicle is found to be 1.03 gH2/km or 0.39 Lge/100 km as gasoline equivalent fuel consumption. The motor is successfully controlled to follow the reference speed and torque, and the motor efficiency is 76.2% including the motor driver. The overall efficiency of the simulated vehicle is calculated as 41.4%.
Keywords: Battery; Fuel cell; Hydrogen; Light electric vehicles; Motor driver